2014
DOI: 10.1542/peds.2013-3806
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Developmental Trends in Sleep Duration During Early Childhood

Abstract: WHAT'S KNOWN ON THIS SUBJECT: A limited number of studies have identified distinct patterns of child sleep duration, which appear to have implications for health and well-being. WHAT THIS STUDY ADDS:This article identifies distinct patterns of sleep duration during early childhood and demonstrates that these have important implications for health-related quality of life. abstract BACKGROUND AND OBJECTIVES: Sleep is important to child development, but there is limited understanding of individual developmental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 30 publications
5
66
2
1
Order By: Relevance
“…A recent longitudinal study mapped the sleep trajectories in around 3000 children from birth to 7 years and found that 60% of the children have atypical sleeping patterns: the majority of whom were initially short sleepers (45%), others were either persistent short sleepers (12%) or poor sleepers (3%). Compared to the typical sleepers, all three groups showed some degree of impaired physical, emotional and social functioning13. The results suggest that, even though some infants with atypical sleep patterns early on eventually develop typical patterns of sleep by 6 or 7 years of age, reduced sleep duration in the first two years of life may have long-term consequences on later developmental outcomes.…”
mentioning
confidence: 78%
“…A recent longitudinal study mapped the sleep trajectories in around 3000 children from birth to 7 years and found that 60% of the children have atypical sleeping patterns: the majority of whom were initially short sleepers (45%), others were either persistent short sleepers (12%) or poor sleepers (3%). Compared to the typical sleepers, all three groups showed some degree of impaired physical, emotional and social functioning13. The results suggest that, even though some infants with atypical sleep patterns early on eventually develop typical patterns of sleep by 6 or 7 years of age, reduced sleep duration in the first two years of life may have long-term consequences on later developmental outcomes.…”
mentioning
confidence: 78%
“…(29, 30) School-age children and adolescents are, in general, less sensitive to sleep disruption. Infants may be somewhat protected as their circadian rhythm is incompletely established, while preschool-age children have newly acquired consolidation of sleep at this developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…Bedtime resistance may impact overall sleep duration and result in increased risk for obesity. Poor sleep during childhood has been associated with reduced cognitive performance, lower quality of life, and secondary effects including impaired family functioning (Chen et al, 2008; Lavigne et al, 1999; Magee et al, 2014). The relationships between child functioning and specific sleep problems in children at high risk for obesity remains unclear in the extant literature.…”
Section: Child Functioningmentioning
confidence: 99%
“…Short sleep duration has been identified as a strong predictor, independent of other obesity risk factors, and most consistently during early childhood (Chen, Beydoun, & Wang, 2008). Longitudinal studies with preschoolers identified 4 distinct sleep trajectories and short sleep duration was found to be predictive of being overweight and poorer physical health (Magee, Gordon, & Caputi, 2014; Touchette et al, 2007). Physiologically, short sleep duration has been associated with increased ghrelin and decreased leptin, in which hormonal changes have been linked with increased appetite (Taheri, Lin, Austin, Young, & Mignot, 2004).…”
mentioning
confidence: 99%